Diseño de radio base multi operadora celular para centro parroquial de Nambacola - Jaramillo Pinta, Sergio René (2023)
This project a multi-operatior cellular base radio was designed with the purpose of providing an alternative solution to the deficient Advanced Mobile Service (AMS) network coverage in rural communities of Ecuador and particularly in the Nambacola parish; these sectors are generally excluded from the coverage projects of the mobile operators, thus this solution is economically viable for the cellular operators, reusing fourth generation UMTS technology which is expected to be dismantled in the coming years in major cities due to the implementation of 5G. The backbone connection is defined by means of a single optical fiber and through which logical tunnels will be implemented to allow interconnection to each of the 3 operators; finally, the rules of operation and maintenance of the radio base are raised. Keywords: Rurals, UMTS, backbone, 5G, logical tunnels.